The Natural Disasters that Struck Baghdad during the Era (334-550 AH / 955-1155 AD) and their Economic, Social, and Urban Impacts (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study deals with the natural disasters that befell Baghdad during the era (344-550 AH / 955-1155 AD) and their economic, social and urban effects. Baghdad witnessed a large number of natural disasters, which exceeded thirty-four. Epidemics and the diseases they carried took lives, and the city and its people were unable to face them, as happened in 423 AH / 1031 AD, as well as in 469 AH / 1076 AD, which were severe, especially in the outskirts of Baghdad,  to the extent that the crops did not find anyone to collect them. In the year 478 AH/1085 AD, the city was swept by a plague epidemic that left more than twenty thousand dead0. In addition, it was exposed to a large number of other disasters, such as earthquakes, lack of rain, and locust waves, which negatively affected to people’s lives and livelihoods.The floods were a major factor in changing the features of Baghdad. Rather, they were among the most severe tools for demolishing its infrastructure. The city was subjected to several floods, the most severe of which were inyears 461 AH / 1068 AD and 466 AH / 1073 AD. As a result, the city lost most of its architecture, so its area shrank, and most of its urbanization was confined to the eastern side, in addition to the “demographic” change of some of its parts, represented by the immigration of the population of the afflicted areas, and, consequently, the ruin and diasapperance of many residential areas
Keywords: Baghdad; Disasters; Earthquake; Flood; Fires